2019
DOI: 10.1111/jorc.12308
|View full text |Cite
|
Sign up to set email alerts
|

Improved outpatient haemodialysis adequacy using queued schedules

Abstract: SUMMARY Background Although technical advances help achieve haemodialysis adequacy, we hypothesise remediable non‐therapy factors exacerbate patient dissatisfaction, non‐adherence to treatment time and failure to meet dialysis goals. Scheduling inefficiencies lead to the total time in the unit far greater than actual treatment time, impacting facility efficiency and patient frustration. Objectives We used queuing theorem principles to optimise schedules by incorporating timing and workflow for every dialysis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…44,45 To reduce staff strain and improve satisfaction, studies have focused on implementing novel staffing schedules, reducing staff-to-patient ratios, or improving training for dialysis clinic staff. [46][47][48] Several of the changes that interviewees suggested in our study to improve their experience, such as joining a unit affiliated with their preferred hospital or having a clean facility, can be addressed at dialysis initiation when patients "shop" for clinics. However, we found that most of the interviewees in our study were not able to play an active role in selecting which units they received dialysis treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 To reduce staff strain and improve satisfaction, studies have focused on implementing novel staffing schedules, reducing staff-to-patient ratios, or improving training for dialysis clinic staff. [46][47][48] Several of the changes that interviewees suggested in our study to improve their experience, such as joining a unit affiliated with their preferred hospital or having a clean facility, can be addressed at dialysis initiation when patients "shop" for clinics. However, we found that most of the interviewees in our study were not able to play an active role in selecting which units they received dialysis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 To reduce staff strain and improve satisfaction, studies have focused on implementing novel staffing schedules, reducing staff-to-patient ratios, or improving training for dialysis clinic staff. 4648…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Balhara et al16 concluded that missing treatments were commonly due to impaired mobility, higher pain severity, depression, and physical limitations, as well as dependence on public transportation to get to dialysis treatments. Patient nonadherence is exacerbated when inefficient scheduling results in dissatisfaction from the total time in the dialysis unit being well beyond the actual treatment time, which can regularly occur in the hospital setting due to staffing inadequacies and reliance on other departments such as patient transportation and environmental services 17…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Barghash and Saleet (2018) evaluated the impact of high lateness and no show percentages when setting appointment schedules. Nappo and Ross (2020) propose staggered appointment schedules with small group of patients rather than two big shifts to increase efficiency and minimize wait times. Klassen and Yoogalingam (2019) investigated the effect of adding mid-level service providers (assistants and nurse practitioners) on patient wait time, flow time and physician service time.…”
Section: Introductionmentioning
confidence: 99%